1999
DOI: 10.1016/s0272-6386(99)70348-3
|View full text |Cite
|
Sign up to set email alerts
|

Indices of activity of the nitric oxide system in hemodialysis patients

Abstract: Arginine deficiency and/or increased levels of circulating nitric oxide (NO) synthesis (NOS) inhibitors can cause reduced NOS, which may contribute to hypertension in patients with end-stage renal disease (ESRD). To test these hypotheses, NO oxidation products (NO 2 + NO 3 = NO x ) and cyclic guanosine monophosphate (cGMP), the vasodilatory second messenger of NO, were measured in the blood, urine, and dialysate effluent of hemodialysis (HD) patients and compared with the blood and urine of healthy subjects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 22 publications
10
59
0
Order By: Relevance
“…1 By this measure, the total amount of NO X 'excreted' in a 24-h period is decreased in patients with end-stage renal disease (ESRD) receiving peritoneal dialysis or hemodialysis, as well as in CKD patients with approximately 25% residual renal function compared with controls ( Figure 1). [2][3][4] Similar conclusions have been reached by Blum et al 5 and Wever and colleagues 6 (the latter group measured conversion of 15 N 2 -labeled arginine to citrulline in people with CKD). Although Lau and co-workers reported increased rates of arginine conversion to citrulline in ESRD patients 7 -perhaps reflecting activation of inducible nitric oxide synthase [NOS] by hemodialysis-most evidence indicates that total NO production is decreased in humans with CKD or ESRD compared with healthy individuals.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…1 By this measure, the total amount of NO X 'excreted' in a 24-h period is decreased in patients with end-stage renal disease (ESRD) receiving peritoneal dialysis or hemodialysis, as well as in CKD patients with approximately 25% residual renal function compared with controls ( Figure 1). [2][3][4] Similar conclusions have been reached by Blum et al 5 and Wever and colleagues 6 (the latter group measured conversion of 15 N 2 -labeled arginine to citrulline in people with CKD). Although Lau and co-workers reported increased rates of arginine conversion to citrulline in ESRD patients 7 -perhaps reflecting activation of inducible nitric oxide synthase [NOS] by hemodialysis-most evidence indicates that total NO production is decreased in humans with CKD or ESRD compared with healthy individuals.…”
Section: Introductionsupporting
confidence: 66%
“…Indeed, renal L-arginine synthesis is significantly reduced (to approximately 40% of normal levels) in CKD patients; 24 however, plasma levels of L-arginine in patients with renal disease are at the low end of the normal range and are always well in excess of the K m of NOS enzymes. [2][3][4] Further, net endogenous L-arginine synthesis is preserved in ESRD patients, 7 presumably because of compensatory increases in production by nonrenal tissues.…”
Section: Regulation Of Substrate Availabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…[8,13,14] While some studies reported ADMA levels 2-6 greater in CAPD patients, [13,14] Kielstein et al did not report any difference of ADMA levels in CAPD patients and healthy subjects. [8] Additionally, there are several reports suggesting increased cardiovascular risk in hemodialysis and CAPD patients with high serum levels of ADMA.…”
mentioning
confidence: 99%